2009
DOI: 10.33151/ajp.7.2.165
|View full text |Cite
|
Sign up to set email alerts
|

The Organisation of Trauma Services for Rural Australia

Abstract: This review discusses the development of trauma care and the retrieval process in Australia, particularly as it impacts on the rural population. In rural and remote settings, trauma is a major cause of death and disability with the death rate from injuries increasing with progressing remoteness. Time is a critical factor in trauma care and the length of time it takes to reach definitive care has a significant impact on patient outcome. In rural areas people have difficulties accessing medical services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…It has been proposed previously that such towns might develop uniquely harmful cultures around alcohol consumption aligned with conceptualizations of masculine identity. 33 More research is required to further investigate the driving factors behind the higher rates of alcohol consumption and harms within rural and regional areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed previously that such towns might develop uniquely harmful cultures around alcohol consumption aligned with conceptualizations of masculine identity. 33 More research is required to further investigate the driving factors behind the higher rates of alcohol consumption and harms within rural and regional areas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, people who sustain severe injuries in a rural area may be taken directly to a larger ED in a metropolitan region. However, direct transport to larger ED and trauma services is often unrealistic given the large distances and length of transport time; therefore, patients are likely to be taken to the local ED first . Another important limitation is the use of a state‐level sample.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients might present to the rural clinician with a wide spectrum of critical conditions, requiring initial stabilisation and transfer to metropolitan tertiary centres for definitive care. Prehospital incidents are common in rural areas, with up to 65% of national road fatalities occurring in rural Australia . A Western Australia study showed that rural locations accounted for one‐third of major trauma cases (injury severity score >15) .…”
Section: Introductionmentioning
confidence: 99%
“…Prehospital incidents are common in rural areas, with up to 65% of national road fatalities occurring in rural Australia. 4 A Western Australia study showed that rural locations accounted for one-third of major trauma cases (injury severity score >15). 5 Whereas transport injuries predominate, other hazards include agricultural and mining industries, as well as envenomations, wildlife-vehicle collisions and environmental hazards.…”
Section: Introductionmentioning
confidence: 99%